Operational Characteristics of Ipoh City Bus Services Route : Ipoh- Ipoh Garden East - Mohd Zin, Nurul Ashikin (Universiti Teknologi PETRONAS, 2010)
The main purpose of the study is documenting and evaluating the operational characteristics of Ipoh city bus services operated for the route Ipoh (Medan Kidd) - Ipoh Garden East (Taman Ipoh Timur). The study divided into three (3) mains parts that are comparison operational characteristics, evaluating bus service performance quality according to Level Of Service framework (LOS) and documentation of users characteristics and perceptions on the provided service. Analysis of the collected data shows 30.9% different value of the actual (current) and the standard design operational parameters. Long waiting and longer cycle are not a desirable condition for the passenger since they have to allocate extra time in their trips plan. The degree of reliability that the user could have on the current service performance indicated by the service performance evaluation that is LOS C. Outcome of the questionnaire survey shows the actual users pattern that dominated by the group of low income (58%) and group of students (43%). These groups utilize the service to travel for works and schools due to the unavailability of transportation for travelling and to reduced travelling cost. This clearly shows by the low score gave by users on the suitability of the bus fare that shows their concern on the travelling cost that they have to spend. Overall, the current provided city bus service considered effective in serving the current transportation demand of Ipoh residents. Further improvements required in the especially in the service performance and provided facilities to attract more users and thus reducing the traffic congestion problem in Ipoh city.